PEMODELAN MATEMATIKA DAN ANALISIS GERAK LABORATORIUM TERBANG BERBASIS PESAWAT AEROMODELING - Izzuddin Fahmi, Muhammad
Skysurfer UAV as one type of Unmanned Aerial Vehicle is need to have good maneuverability to be able to carry out missions. This UAV can be used as teaching material to analyze the dynamics of aircraft motion. Unfortunately, maneuvering is a movement that has high speed is difficult to control. So modeling is needed to facilitate the operator in controlling the maneuvering motion. This study aims to analyze the dynamics of the system that is able to do the UAV model with the given maneuver control so that the aircraft can maneuver according to the control commands.